At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
12=12
Step-by-step explanation:
2a = b
a -3b =12
To solve, set one of the equations equal to zero. The first equation is actually already set to 0.
b = 2a
Now you can plug this equation into the other one, by substituting the b in the equation with this.
a -3b = 12
a – 3(2a) = 12
Now all you have to do is distribute the 3 (multiply the number outside the parenthesis, 3 in this case, by everything inside).
a – 6a = 12
Combine like terms. Since we have 1 positive a and 6 negative ones, we subtract the two numbers without the signs
6-1 = 5
And take the sign of the larger number. Since 6 is large and 6 is negative, we are left with
-5a = 12
Now solve for a, which in this case means dividing both sides by -5
a = -12/5
Simplify
a = -2.4
Now that you have a, it’s easy to find b
b = 2a
b = 2(-2.4)
b= -4.8
Now you check your work by plugging your new a and b into either equation to see if it’s true.
-4.8 = 2(-2.4)
-4.8 = -4.8
And just for laughs let’s try the other equation
a -3b =12
-2.4 – 3(-4.8) = 12
Distribute the 3 again. Remember that when two negative numbers are multiplied they become positive.
-2.4 +14.4 = 12
12 = 12
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.